Evaluation of flattening-filter-free and flattening filter dosimetric and radiobiological criteria for lung SBRT: A volume-based analysis - Wu, Junxiang; Song, Hongchang; Li, Jie; Tang, Bin; Wu, Fan (Frontiers in Oncology, 2023)
The use of volumetric modulated arc therapy (VMAT) with flattening-filter-free (FFF) beams is becoming more prevalent in lung cancer stereotactic body radiotherapy (SBRT). The aim in this study was to assess the impact of dosimetric and radiobiological differences between FFF and flattening filter (FF) beams for lung SBRT based on the target volume. A total of 198 lung stereotactic body radiation therapy treatment plans with FFF beams and FF beams were retrospectively selected for this study. For all plans, the prescribed dose was 50 Gy/5 fractions, and the dose volume histogram (DVH) for the target and organs at risk (OAR) and the normal tissue complication probability (NTCP) of the lung were recorded and compared. Moreover, monitor units (MUs), the beam on-time and the treatment time were evaluated. The study was performed following the Radiation Therapy Oncology Group (RTOG) 0813 and 0915 protocols. No significant differences in D90, coverage rate (CR) or conformity index (CI) of the target were observed between FFF beams and FF beams (p>0.05). The D2, R50% and gradient index (GI) for the target improved with FFF beams compared with FF beams (p<0.05). FFF beams also significantly reduced the dose for the lung, heart, spinal cord, esophagus and NTCP of the lung (p<0.05), compared with FF beams. However, there was no significant difference in sparing of the trachea (p>0.05). The mean MUs, beam on-time and treatment time were 1871±278 MUs, 3.2 ±0.2 min and 3.9 ±0.3 min for FFF beams, and 1890±260 MUs, 4.2±0.3 min and 4.8 ±0.4 min for FF beams, respectively. The FFF beam technique for lung SBRT with VMAT results in a better dose fall-off, better dose-sparing of OAR, lower NTCP of the lung and a shorter beam on-time compared with the FF beam technique. Additionally, the improvement in target and OAR-sparing for FFF beams was increased with increasing target volume.